Stories of human exceptionalism : writing through the impasse between care and domination : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Sociology, Massey University, Albany, Aotearoa New Zealand - Ashley, Nicole (Massey University, 2023)
The coalescing socio-political and environmental crises characterising the epoch of the Anthropocene raise fundamental questions about what it means to be human. Underpinning these tensions is a tendency that has become predominant within Western societies: an assumption that humans are 'above' the natural world, as if somehow 'exceptional'. This strains our relationship with the other. Human exceptionalism culminates in the impasse between care and domination. Relations of care and domination are inextricable: attempts to care for the other cannot be divorced from the forms of domination upon which those efforts are predicated. Yet as Alenka Zupančič (2017) affirms, this contradiction is not inherently problematic. What is problematic is when this contradiction is disavowed, for this is when human exceptionalism is reified. In questioning how we might care in a way that does not tacitly reinforce exceptionalist forms of dominance, I draw upon Zupančič's object-disoriented ontologies as a means of working through these interdisciplinary concerns. This involves attending to those objects that object to the discursive rationalities that we script about them. In a move that turns Zupančič's theoretical postulations into a distinct methodological orientation, I use autoethnography—specifically, an object-disoriented autoethnography—to work through experiences within my own life that elucidate the impasse between care and domination and thereby the disavowal of our exceptionalism. These experiences demonstrate three fields of social interaction that are complicit in the reproduction of human exceptionalism: the university's administration of an ethical subject; the making and unmaking of nature through conservation programmes; and the practices of death involved in the sustaining of life. Taking my place within the contradictions I seek to understand, this research thereby puts my own subjectivity on the line. In doing so, I illustrate how object-disoriented autoethnography enables a means of working with the limit points of our exceptionalism. In the process of re-scripting our stories anew, new insight can be revealed. In this instance, a generative capacity lies in the naming of the forms of violence encapsulated within care.
Keywords: 440104 Environmental anthropology; 500304 Environmental philosophy